Analysis of reproductive health training at the undergraduate level - Jeffersson, Lucy (2015)
The teaching of reproductive health should be a framework in relation to knowledge of the demographic situation and population dynamics of a country, its social and economic development of their health policies and education, the cultural context that characterizes and - I enter this context- the situation of women. It is also important to consider the moral and ethical standards that must reach the student in pre-professional preparation that allows assume responsibility for preventive, curative and rehabilitative health activities in their actions.